Demographic and clinical profile of patients with juvenile onset open angle glaucoma in southwestern Nigeria (2011)
Background: This was a non-comparative, retrospective review of patients diagnosed with juvenile open angle glaucoma (JOAG) in the eye clinic of a tertiary hospital in southwestern Nigeria. Objective: To document the demographic characteristics, clinical features and treatment outcome of the patients diagnosed with JOAG. Materials and Methods: Data were extracted from the clinical record of patients diagnosed with JOAG in the eye clinic of the University College Hospital, Ibadan, Nigeria, between January 2001 and December 2005. Such data included the basic demographic data, the clinical characteristic of the patients and the outcome of their treatment. Results: Twenty-nine patients were reviewed, which represents 3.4% of all newly diagnosed glaucoma patients seen in the out-patient section of the eye clinic of the University College Hospital, Ibadan, over the period reviewed. Eight (27.6%) patients were aged 20 years and below. The mean age was 25.1 ± SD 6.0 years. Eighteen (62.1%) had visual acuity of 6/18 or worse in the better eye at the time of presentation. The mean intraocular pressure (IOP) of the patients at presentation was 32.3 ± SD 15.2 mmHg. Eight (27.6%) patients defaulted within 6 months of presentation. The mean IOP for the 21 patients who were followed up on treatment for a mean period of 9.6 months was 17.0 ± SD 6.0 mmHg. Conclusion: Most patients with JOAG in this review presented with advanced form of the disease. Early detection through parent-driven school eye health program and community-based case detection could help in reducing the scourge arising from JOAG among our population.